INFLUENCE OF INFORMATION COMMUNICATION TECHNOLOGY ON PERFORMANCE OF PROCUREMENT AMONG PARASTATALS IN KENYA - Wawuda, Jennifer; Mwangangi, Dr, Patrick (International Journal of Supply Chain and Logistics, 2018)
Purpose: The purpose of the study was to examine the influence of ICT on performance of procurement with an aim of making recommendations on proper use of ICT. Methodology: This study adopted a descriptive research design approach targeting heads of procurement and ICT at the 187 parastatals. The study preferred this method because it allowed an in-depth study of the subject. To gather data, structured questionnaire will be used to collect data from a sample of one hundred and thirty (130) respondents, who were selected using simple random sampling, from the four strata. Once collected, data was analyzed using descriptive and inferential statistics. Quantitative data was analyzed using multiple regression analysis. The qualitative data generated was analyzed by use of Statistical Package of Social Sciences (SPSS) version 22. Results: The findings of the study indicated that inventory management systems, electronic vendor evaluation, electronic payments and electronic sourcing have a positive relationship with procurement performance among parastatals in Kenya. Conclusion: Based on the study findings, the study concludes that performance of procurement among parastatals can be improved by inventory management systems, electronic vendor evaluation, electronic payments and electronic sourcing. Policy recommendation: The study recommended that public institutions should embrace information communication technology so as to improve performance and further researches should to be carried out in other public institutions to find out if the same results can be obtained.